A imigração alemã pela mimética de A ferro e fogo : a ficcionalização da história no romance de Josué Guimarães - Ortiz, Eduardo (2022)
History and Literature are disciplines that transit very close to each other, and despite the existence of their own norms and discursive frameworks that differentiate them, genres such as the historical novel insist on defying such rules by configuring themselves as a kind of intermediate narrative. Our research seeks to understand this process of construction of the narrative of the historical novel through A ferro e fogo: tempo de solidão, and A ferro e fogo: tempo de guerra. For that, we elaborated a comparative study between the novels of Josué Guimarães, and A imigração alemã e o Rio Grande do Sul and, L'administration de la Province du Rio Grande do Sul de 1829 à 1847, by Jean Roche, História do Rio Grande do Sul, by Danilo Lazzarotto e Viagem Militar ao Rio Grande do Sul, by Conde Gaston D'Orleans d'Eu. To give greater depth to our analysis, we also investigate the traces left by the novelist in the copies of the historiographical studies that compose his collection – ALJOG/UPF –. Thus, we started to approach in our research different themes, ranging from the beginnings of the occupation of the province, since many of these episodes end up impacting the lives of newcomers, through the arrival and establishment of these immigrants, the rapid development of the Colony of São Leopoldo, the social organization of the Germanic peoples, even themes referring to events such as the Second Cisplatine War, the Farroupilha War, and the Paraguayan War, always emphasizing the participation of Germans and their descendants in these conflicts. Thus, we were able to conclude that Josué Guimarães, through his ideological position, sought to include disadvantaged groups, presenting in his narrative, which can also be read as history by the non-academic public, the participation of different peoples, who until the moment of production of A ferro e fogo, found themselves on the margins of the historiography considered “official”.